Clima y concentraciones de polen de gramíneas en el País Vasco - Rasilla Álvarez, Domingo Fernando (Geographicalia, 2021)
Information regarding air quality in Spanish cities rarely incorporates organic particles, from which pollen is a fundamental component, responsible for numerous respiratory pathologies and a good marker of environmental changes. This contribution examines the links between grass pollen measured at the three Basque capitals and atmospheric conditions, both locally and regionally. The results suggest that a substantial part of the grass pollen measured at the Basque Country comes from nearby areas outside that Autonomous Community, pushed by easterly and southerly winds and SW and SSE circulation types .